Hydrogen electrochemistry in unconventional settings: protic ionic liquids, closed bipolar electrodes and ultra-high vacuum - Goodwin, Sean (2017)
Most commonly, electrochemical experiments are carried out at room temperature, in aqueous or organic electrolytes that contain both an analyte and a supporting electrolyte. However, voltammetry has also been undertaken in a wide variety of more unusual or extreme settings; aluminium smelting involves electrolysis at over 900 °C, bipolar electrochemical experiments often require the absence of supporting electrolyte, and dopamine releases in rats have been monitored by in-vivo electrochemistry of the rats’ brains. In this thesis, unconventional electrochemical investigations are described. These include electrochemical experiments in protic ionic liquids (PILs), in ultra-high vacuum and using closed bipolar electrodes. In each case, the experiments were undertaken in order to further research into energy storage systems. Although electricity generation from renewable sources such as wind and solar is good for the environment, these sources are intermittent, and we need to develop efficient ways of storing this energy to compensate for the intermittency. The use of PILs, as well as closed bipolar electrodes, offer promising avenues to improving the efficiency of energy storage devices. Using hydrogen as a means of energy storage is one route to solving the problem of intermittency of renewable energy sources. Chapter 3 is a study of hydrogen oxidation at Pt ultra-microelectrodes in one PIL, diethylmethylammonium trifluoromethanesulfonate, [dema][TfO]. Voltammograms of hydrogen oxidation show both a diffusion-limited plateau and an ‘additional’ plateau at lower overpotentials than the former. Different theoretical models are used to simulate this reaction, and the reaction is found to be inhibited by adsorption of under-potentially deposited hydrogen, Hupd. In Chapter 4 a voltammetric method is developed for determining the concentration of precursor acid and base in PILs. The concentration of precursor acid is found to vary significantly depending on the method used to synthesise the PIL, and recommendations are made on how to synthesise a PIL with minimal precursor acid present. The base, by contrast, is found to evaporate out of the PIL very easily. In Chapter 5, voltammetry of two PILs is undertaken under conditions of ultra-high vacuum. Precursor acids in the PILs are found to be relatively stable even under vacuums of 10-8 mbar. By using in-line mass spectrometry, the products of [dema][TfO] oxidation are also investigated. Finally, closed bipolar electrodes are used in Chapter 6 to spatially separate H2 and O2 evolved in a water electrolyser. By separating these gases, the risk of the two species mixing is removed, making the electrolyser a much safer device to operate, particularly at low current densities.